Diffusion Control in Single-Site Zinc Reticular Amination Catalysts - Cirujano, Francisco G; López-Maya, Elena; Almora-Barrios, Neyvis; Rubio-Gaspar, Ana; Martín, Nuria; Navarro, Jorge A R; Martí-Gastaldo, Carlos (Inorganic chemistry, 2020)
Zn-containing metal-organic frameworks have been used for the first time as heterogeneous catalysts in the amination of C-Cl bonds. The use of extended bis(pyrazolate) linkers can generate highly porous architectures, which favor the diffusion of amines to the confined spaces with respect to other imidazolate frameworks with narrower pore windows. The N Zn nodes of the Zn-reticular framework show comparable activity to state-of-the-art homogeneous Zn amination catalysts, avoiding the use of basic conditions, precious metals, or other additives. This is combined with long-term activity and stability upon several reaction cycles, without contamination of the reaction product.